Klotho Polymorphism in Association With Serum Testosterone and Knee Strength in Women After Testosterone Administration - Ekström, Lena; Knutsson, Jona Elings; Stephanou, Christina; Hirschberg, Angelica Lindén (Frontiers in Physiology, 2022)
Administration of testosterone (T) is associated with increased serum T concentrations and improved physical performance in women. However, the inter-individual variation in T concentrations after T treatment is large and may in part be due to genetic variations. Serum T, as well as dihydrotestosterone (DHT), androstenedione (A) and the T/A ratio have been suggested as promising doping biomarkers for testosterone intake. Here, polymorphisms in androgen metabolic enzyme genes have been investigated in healthy women prior to and after ten weeks administration of testosterone cream. Klotho is a protein that has been associated with anaerobic strength and here a genetic variation in klotho gene was studied in relation to performance as measured by isokinetic knee strength, as well as to serum androgen disposition. The AKR1C3 genotype (rs12529) was associated with serum T levels at baseline, whereas serum concentrations post T treatment did not differ between genotypes. The SLCO2B1 (rs12422149) and UGT2B17 deletion polymorphisms were not associated with serum concentration of either T, DHT or A. The klotho polymorphism (rs9536314) was associated with serum concentrations of both total T and T/A ratio after T administration. Individuals with the GT genotype increased T concentrations and T/A ratio more than women homozygous for the T allele. No significant difference in the association of klotho genotype with knee muscle strength was observed between placebo and T treatment. However, individuals homozygous for the T allele showed higher isometric mean torque scores at exit than GT subjects after T administration.